The Relationship Of Learning Interest And Parents' Trust With The Results Of Learning Indonesian Language Online In Class Iv at Cluster 2 Elementary School Kapanewon Sewon Bantul - MM Eni Suryati (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2022)
This study aims to determine the relationship between learning interest and parental care with online learning outcomes of Indonesian language for the fourth grade of SD Cluster 2 Kapanewon Sewon Bantul. This study uses a quantitative approach or data analysis with a correlational design. This study consists of 3 variables which consist of 2 independent variables, namely interest in learning (X1) and parental care (X2) and consists of 1 variable, namely the results of Indonesian online learning (Y). The subjects of this study consisted of the population, namely all students in six elementary schools in the Sewon sub-district which presented 890 students and a sample of 192 fourth grade students at SD Distance, SD Sawit, SD Distance 3, SD Blunyahan 1, SD Blunyuhan 2, and SD Muhammadiyah Pendowo. Sampling using purposive random sampling technique. Data collection methods used are questionnaires and tests. The data analysis technique used statistical calculation of product moment correlation. The results showed: First, based on statistical analysis between interest in learning and the results of online learning Indonesian, the correlation coefficient (r) = 0.502. This means that there is a positive and significant relationship (0.000 < 0.05) between interest in learning and Indonesian online learning outcomes of 25.2%. Second, statistical data analysis of the relationship between parental care and Indonesian online learning outcomes obtained a correlation coefficient (r) = 0.506. This means that there is a positive and significant relationship (0.000 < 0.05) between parental care and Indonesian online learning outcomes of 25.6%. Third, based on statistical data analysis of the relationship between interest in learning and concern for parents together with the results of online learning Indonesian, it is obtained a double correlation coefficient (R) = 0.575. This means that there is an interest in learning and concern for parents who together have a positive and significant relationship (0.000 < 0.05) with online learning outcomes for Class IV students of SD Cluster 2 Kapanewon Sewon by 33.1% and the rest 66 , 9% Influenced by other factors.